Source Studies as a Theoretical Base of Historical and Pedagogical Research - Nataliya Stetsenko (Pedagogical Discourse, 2013)
The general issues of source studies as a separate branch of historical science are considered in the article.The main definitions of the notions «a historical source», «a historical and pedagogical source» are defined in the article. The article deals with conditional classification of historical and historical-pedagogical sources. The stages of the study of historical-pedagogical sources: classifications, analysis, synthesis, are investigated.